THE ROLE OF DIGITAL TOOLS IN ONLINE ENGLISH LANGUAGE TEACHING. (International journal of artificial intelligence, 2026)
The rapid development of digital technologies has significantly transformed the field of education, particularly in the teaching and learning of foreign languages. Online English language teaching has become increasingly widespread, making digital tools an essential component of modern pedagogy. These tools support interactive learning, enhance learner motivation, and provide access to authentic language resources. This article examines the role of digital tools in online English language teaching, focusing on their pedagogical benefits, types, and practical applications. Special attention is given to how digital platforms contribute to the development of language skills, learner autonomy, and teacher effectiveness. The study also discusses challenges related to the use of digital tools and suggests ways to overcome them. The findings highlight that when used appropriately, digital tools can significantly improve the quality and effectiveness of online English language instruction [1].